2009
DOI: 10.1371/journal.pone.0008396
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Induced IL-23 and IL-1β Allow for IL-12 Production by Monocytes and Mφ1 through Induction of IFN-γ in CD56+ NK/NK-Like T Cells

Abstract: BackgroundThe type-1 cytokine pathway plays a pivotal role in immunity against intracellular bacterial pathogens such as Salmonellae and Mycobacteria. Bacterial stimulation of pattern recognition receptors on monocytes, macrophages and dendritic cells initiates this pathway, and results in the production of cytokines that activate lymphocytes to produce interferon (IFN)-γ. Interleukin (IL)-12 and IL-23 are thought to be the key cytokines required for initiating a type-1 cytokine immune response to Mycobacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…Indeed, although the relatively low NK cell expression of IL-1RI, as compared with ILCs, has led to the general consensus that NK cells are negative for this receptor (30), our findings are in line with previous reports showing that human NK cells express detectable levels of IL-1RI and that IL-1b has biological activities on human NK cells (28,29,31). In particular, it has been also reported that IL-1b acts as a synergistic cytokine with IL-12, IL-15, and IL-23 for IFN-g production (28,31,32) and, to the best of our knowledge, this study reports for the first time that IL-1b also increases human NK cell cytotoxicity via the induction of NKp44 expression. Indeed, our results demonstrate that: 1) M1-primed NK cells have a significantly higher expression of IL-1RI compared with their resting counterparts; 2) the incubation of NK cells in vitro with rhIL-1 upregulated NKp44; 3) the masking of IL-1b and IL-1RI decreased NKp44 expression on M1-primed NK cells; and 4) the use of the inflammasome inhibitor glibenclamide inhibited M1 production of IL-1b, thus preventing the M1-induced upregulation of NKp44.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, although the relatively low NK cell expression of IL-1RI, as compared with ILCs, has led to the general consensus that NK cells are negative for this receptor (30), our findings are in line with previous reports showing that human NK cells express detectable levels of IL-1RI and that IL-1b has biological activities on human NK cells (28,29,31). In particular, it has been also reported that IL-1b acts as a synergistic cytokine with IL-12, IL-15, and IL-23 for IFN-g production (28,31,32) and, to the best of our knowledge, this study reports for the first time that IL-1b also increases human NK cell cytotoxicity via the induction of NKp44 expression. Indeed, our results demonstrate that: 1) M1-primed NK cells have a significantly higher expression of IL-1RI compared with their resting counterparts; 2) the incubation of NK cells in vitro with rhIL-1 upregulated NKp44; 3) the masking of IL-1b and IL-1RI decreased NKp44 expression on M1-primed NK cells; and 4) the use of the inflammasome inhibitor glibenclamide inhibited M1 production of IL-1b, thus preventing the M1-induced upregulation of NKp44.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, these chemokines enhance the cytolytic (123). Salmonella was also shown to induce the production of IL-1β and IL-23 by macrophages favoring the production of IFN-γ by NK cells (124). A similar synergy between IL-1β and IL-12 leading to an enhanced production of IFN-γ was also reported in response to LPS and L. monocytogenes (109).…”
Section: Nk Cells and Accessory Cytokinesmentioning
confidence: 63%
“…Previous publications have also described a role for IL-12-related cytokines in macrophage-NK cell interactions. Specifically, macrophage-derived expression of IL-23 and IL-27 induced the production of IFN-γ and GM-CSF in NK cells [31][32][33]. Although the production of IL-27 was monitored in IFN-λ-stimulated macrophages, the effects on NK-cell function were not explored in this study.…”
Section: Discussionmentioning
confidence: 98%